Usability of lithuanian fusible clay for sintered ceramics/Lietuvos teritorijoje esančių lengvai lydžių molių tinkamumas statybinei sukepusiajai keramikai - Žurauskienė, Ramunė; Mačiulaitis, Romualdas; Petrikaitis, Fabijonas (Journal of Civil Engineering and Management, 2001)
Facade articles of ceramics being produced recently in Lithuania are hygroscopic and are not resistant to humid winters predominant in territory of our country. It is possible to prolong longevity of the exterior finishing of buildings by using sintered building ceramic which absorbs up to 5% moisture (LST 1458) and according to service frost resistance conforms to A.2. and A.3. categories of durability (LST 1428.19:1998). The clay available in Lithuania is fusible, sintering interval of the clay is quite narrow (≤ 60 °C). It is used for production of common and finishing bricks, blocks, roof tiles. Bricks of sintered ceramic and clinker are not produced in Lithuania. The aim of the work was to obtain sintered ceramics by using local raw materials together with not expensive imported additives. For the research clay of Ukmergė deposits was selected according to three-phase diagram of Vinkler [4] and Avgustinik's classification [5] of chemical functional composition (Fig 3) and clay from Rokai deposit having different granulometric composition. High-melting clays from Vesiolov's and Nikiforov's deposits in Ukraine were used in the work (Table 1). Feldspar and pearlite from Ukraine (Table 1) as flux additives were added into forming mass to achieve lower ceramic body formation temperature and to increase amount of melt mass. Non-plastic materials used in the work are: crushed brick and waste moulding sand from “Centrolitas” foundry, which includes 5,5–6% of quartz sand binded by liquid glass. Grading of the sand is presented in Table 3. Forming mixtures, composition of which is given in Table 4, were prepared. Maximum temperature for batching of samples is 1070 °C, the temperature corresponds with average sintering temperature of local clays; burning time is 40 hours with exposure of 7 hours to maximum backing temperature. The most sintered ceramic body was obtained in samples No 8–11 out of all moulding mixtures used in the work (Table 5). The samples had water absorption content of 2–3%. At frost resistance test (by one side freezing) samples No 2, 3, 7–11 was without any signs of break-up after 75 cycles. These samples correspond to category A.2. of longevity (according to LST 1428.19:1998). The samples No 8–11 are being tested by volume freezing thawing achieved 180 cycles without any break-up (No 9—260 cycles) and they are still under the test. The samples has the highest amount of reserved pores (55–73%), compression strength is 17–28 MPa, bending strength is 12–14 MPa. Physical-mechanical properties of specimens No 5, 6 and No 10 differs significantly. First specimens were produced out of forming mass, the composition of which consisted of 55% Rokai clay and 20% of high-melting clay, and forming mass composition of specimen No 10 consisted of 70% of Ukmerge clay and 30% of high-melting clay. Clay from Ukmerge is more suitable for production of sintered ceramics according to the diagrams examined above. Properties of this specimen conforms to requirements applied for sintered ceramic shiver. Addition of flux additives into forming mass did not improve physical-mechanical properties of ceramic shiver. The highest amount (16%) of the additive was added into forming mass No 7. Flux additives should comprise up to 20–30% of forming mass [8], but in this case price of such bricks would be increased significantly. The main conclusion: It is possible to obtain sintered building ceramics out of low-melting clays with additives suitable for exterior finishing of buildings.Article in Lithuanian.First Published Online: 30 Jul 2012